Antibody against Helicobacter pylori CagA and VacA and the risk for gastric cancer. - Yamaoka, Y (1999)
AIM: Helicobacter pylori is associated with gastric cancer. Our aim was to investigate whether CagA or VacA seropositivity provides additional risk for gastric cancer. METHODS: Sera from 110 gastric cancer patients were sex and aged matched with asymptomatic controls. H pylori status was determined by IgG enzyme immunoassay (HM-CAP EIA); CagA status was assessed by enzyme linked immunosorbent assay (ELISA) (OraVax) and immunoblotting (Chiron), and VacA status by immunoblotting using recombinant proteins as antigens. RESULTS: H pylori infection was associated with an increased risk of gastric cancer (odds ratio (OR) = 2.19, 95% confidence interval 1.17 to 4.1). Subgroup analysis showed a significant association with intestinal type (OR = 2.94, 1.35 to 6.41), distal type (OR = 2.97, 1.39 to 6.33), early gastric cancer (OR = 3.74, 1.54 to 9.06), and age < or = 55 years (OR = 8.33, 2.04 to 34.08), but not with diffuse type (OR = 0.83), proximal type (OR = 1.0), advanced gastric cancer (OR = 1.13), or age > 55 years (OR = 1.40). Serum CagA IgG and VacA antibody positivity was present in similar proportions in patients with and without cancer, with no significant differences in histological classification, clinical stage, or location (p > 0.3). CONCLUSIONS: H pylori infection causes chronic gastritis and is associated with the development of gastric cancer. Neither CagA nor VacA seropositivity added additional information or stratification.